Towards the Sustainable Decommissioning of Fixed Platforms by Aligning Ecosystem Services and Wind Generation: A Brazilian Case - Vieira Barboza, Douglas; Jasmim Meiriño, Marcelo; da Silveira Barros, Sérgio Ricardo; Fernandes Bella, Ricardo Luiz (International Journal of Energy Economics and Policy, 2023)
Brazilian legislation, as well as others around the world, determines that oil platforms, mainly fixed, must be decommissioned at the end of the feasibility of exploring the oil field, however, it is not common to consider the loss of ecosystem services that sustain life, the biodiversity and make resources available to humans. Considering the importance of the ecosystems that developed in the substructures of platforms, this work proposes a solution to maintain ecosystem services together with the development of clean, economically viable wind energy generation. For this, a proposal is built based on climatological, geographic, and wind power generation market data that seeks to demonstrate the financial viability of the specific case of the Robalo 1 Platform, which is located about 50 kilometers from other platforms to be decommissioned, in the Sergipe-Alagoas Basin, Brazil. It was found that when minimally valuing ecosystem services such as artificial reefs and integrating wind generation for the non-decommissioning of the fixed platform substructure, from the point of view of net present value, the project proves to be viable.